THE ROLE OF INTERNAL CONFLICTS AND DEFENSE MECHANISMS IN THE PSYCHOLOGY OF MEDICAL STUDENTS - Mirzayeva Umida Bosit qizi; Olimjonov Muhammadbobur Rasuljon og’li (Bright Mind Publishing, 2025)
This article analyzes important aspects of the psychology of medical students, in particular, the internal conflicts, stress and defense mechanisms they encounter during their studies. Detailed information is provided on the psychological difficulties of students entering a medical university in adapting to academic pressure and a new social environment, as well as internal conflicts that arise in the process of professional formation. The article studies what psychological defense mechanisms students use against stress, the effectiveness of these mechanisms and their role in personal formation. The importance of psychological support in a medical university and its role in maintaining the mental stability of students is emphasized. The possibilities of improving the mental health of students through psychological counseling centers, stress-reducing trainings and the mentor-student system are considered. This work demonstrates the importance of a psychological support system for medical students and indicates the need to further develop psychological support.
Keywords: Medical students, psychological stress, internal conflicts, defense mechanisms, academic pressure, adaptation, mental stability, psychological support, sublimation, repression, rationalization, projection, professional formation, stress-reducing training, mentor-student system.